Pembinaan Mental Keagamaan dan Keterampilan Terhadap Gelandangan dan Pengemis di Balai Pungai Sejahtera Binjai - Irwansyah (Ikatan Da'i Indonesia, 2024)
This research aims to explore the mental religious and skills coaching applied at UPTD Balai Pungai Sejahtera Binjai to homeless people and beggars (gepeng). Qualitative methods are used to understand the effectiveness of the coaching programme. The results show that religious mental coaching helps the mentees build a stronger spiritual awareness, while skills training provides opportunities for them to be economically independent. The study recommends strengthening the integration between spiritual and skills coaching to ensure the sustainability of the rehabilitation impact.